2021
DOI: 10.4049/jimmunol.2000455
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept Promotes Regulatory B Cell Functions, Enhancing Their Ability to Reduce the Th1 Response in Rheumatoid Arthritis Patients through the Production of IL-10 and TGF-β

Abstract: Abatacept mimics natural CD152 and competes with CD28 for binding to CD80/CD86 on APC, such as B cells, thereby preventing T cell activation. However, its potential impact on B cells has not been identified. The aim of this study was to assess whether abatacept can potentiate the immunoregulatory properties of B cells in vitro and in patients with rheumatoid arthritis (RA). T and B cells from healthy controls were purified. The suppressor properties of B cells in the presence of abatacept or control IgG1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In the atherosclerotic plaque, T cells produce various cytokines that may further contribute to plaque formation [ 33 ]. As ABT has been shown to inhibit T-cell activation, it could potentially reduce plaque scores [ 34 ]. Reportedly, plaques in unstable angina patients present clonally expanded peripheral blood CD4 T cells lacking CD28 expression (CD4 + CD28 null ) [ 35 ], which are also increased in patients with RA [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the atherosclerotic plaque, T cells produce various cytokines that may further contribute to plaque formation [ 33 ]. As ABT has been shown to inhibit T-cell activation, it could potentially reduce plaque scores [ 34 ]. Reportedly, plaques in unstable angina patients present clonally expanded peripheral blood CD4 T cells lacking CD28 expression (CD4 + CD28 null ) [ 35 ], which are also increased in patients with RA [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 53 However, the flow cytometry results showed no statistically significant difference in Treg frequencies between HC and RA patients, which might be related to the different effects of conventional and biological DMARDs on Tregs in RA patients. 54 57 A number of studies have shown that treatment of RA patients with some but not all of DMARDs, such as methotrexate, tumor necrosis factor-α inhibitors (TNF-αi), adalimumab, and etanercept can restore the regulatory functions of Tregs and increase the frequency of these cells through various mechanisms. 54 , 55 , 58 , 59 Therefore, the effects of OLEU on Tregs could be influenced by treatment of RA patients with various DMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of TGF-β can easily lead to various diseases, including fibrosis, chronic inflammation and malignant tumors [61]. Recent studies have shown that both regulatory T cells (Treg) and B cells (Breg) can produce TGF-β through the endocrine pathway, which can promote the transformation of the macrophages from pro-inflammation into anti-inflammation [62,63].…”
Section: Signal Pathways That Are Tightly Linked To Anti-inflammatory...mentioning
confidence: 99%